From the ground up : the history of mining in Utah - Whitley, Colleen, 1940- (Utah State University Press, 2006)
Despite all mining has done and meant in Utah, there has not been, until now, a book that surveyed its history in Utah. This collection of essays by leading experts is divided into three comprehensive parts. Part I looks at the geology that has produced extractable minerals, the economic history of the industry, and the lore of mines and miners. Part II reviews the history of a handful of particularly significant mineral industries: salines, coal, uranium, and beryllium. The last part takes a region-by-region approach to survey the important, primarily for hard-rock mining, areas of the state.